PENGARUH MASA PERIKATAN AUDIT, PERGANTIAN AUDITOR, UKURAN PERUSAHAAN, SPESIALISASI INDUSTRI, KEPENTINGAN KLIEN TERHADAP KUALITAS AUDIT DENGAN KOMITE AUDIT SEBAGAI VARIABEL MODERASI (Studi Empiris pada Perusahaan Sektor Keuangan Listed di BEI Tahun 2014-2017) - Dhazira Yola Tengku; Hardi Hard; Diyanto Volta (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2019)
This research aims to find empirical evidences regarding the effect ofaudit tenure, auditor switching, capital size, industry specialization, and clientimportance on audit quality with audit committee as a moderating variable. Thesample of this research is 232 financial statements from 58 financing companieslisted in Indonesia Stock Exchange (IDX) in 2014-2017. Samples are used bypurposive sampling method. Data analysis used multiple linear regression andmoderated regression analysis method (MRA). Results of the test showed thataudit tenure, capital size, industry specialization, and client importance an effecton audit quality. Auditor Switching had no effect on audit quality. This researchfind evidence that has interaction between audit tenure, auditor switching, andindustry specialization with audit committee an effect on audit quality. Theinteraction between the capital size and client importance with audit committeehad no effect on audit quality.Keywords : Audit Quality, Audit Tenure, Auditor Switching, Capital Size,Industry Specialization, Client Importance, Audit Committee.